An Engel–Kollat–Blackwell model application on restaurant clientele purchase decision-making processes in commercial eateries in Kakamega County, Kenya - Simon O. Were (Research in Hospitality Management)
Restaurant clientele have a task of making critical decisions concerning their choices of food and drinks. The decision-making process involves, firstly, the selection of the restaurant in which to have a meal and, secondly, the selection of food items from the menu to constitute their meals. Thus, it requires cognitive and physical effort for restaurant clientele to make decisions concerning their restaurant choices and ultimately a final purchase decision. This study applied the Engel–Kollat–Blackwell-consumer purchase decision model to investigate restaurant clientele’s purchase decision-making process among commercial eateries in Kakamega County in Kenya. For the purpose of this study, a five-stage customised EKB model was applied. The study employed a descriptive research survey design, while Fisher’s formula was utilised, giving a sample size of 384 respondents. The study results show a high positive correlation (R = 0.892) between the study variables. The study results indicate that 79.6% of the total variation in consumer ratings was because of the restaurant customer purchase decision-making process, in addition to the overall regression model predicting the outcome variable (p < 0.05). In relation to the contribution of studied predictor variables, a manual search gave the greatest contribution (B = 0.545, p < 0.001, t = 9.105), while sense of belonging/ class of the eatery gave the least contribution (B = −0.584, p < 0.001, t = −12.505). To yield positive results, eatery managers will be required to adjust these predictor variables depending on the contribution of each on the outcome variables, given the predictor variables to be tested account for the most variance in the outcome variable.